EFFECT OF FOLIC ACID SUPPLEMENTATION ON HOMOCYSTEINE LEVEL IN POSTMENOPAUSAL WOMEN - Sultan, Noreen; Khan, Mudassir Ahmad; Malik, Salman (Journal of Ayub Medical College Abbottabad, 2007)
BACKGROUND: Hyperhomocysteinemia is an independent risk factor for atherosclerotic diseases including Ischaemic heart disease, stroke and peripheral vascular disease. Homocysteine (Hcy) is an intermediate formed during the catabolism of essential sulphur containing amino acid methionine, increased Hcy is associated with endothelial dysfunctions in healthy human. Plasma Hcy is significantly lower in premenopausal women than young men but after menopause basal homocysteinemia increases significantly in women approaching those in men. Several studies showed that hyperhomocysteinemia to be stronger risk factor for CHD (Coronary Heart Disease) in women than men. It seems likely that altered hormonal status and age related low folate intake are responsible for this. The present study was designed to evaluate the effect of folic acid supplements for six months, on Hcy level in postmenopausal women. Methods: Hcy was estimated by Flourescence Polarization Immunoassay (FPIA). Results: There was a significant (p<0.001) decrease in Hcy level after six months of folic acid supplements. Conclusion: Hcy is an independent risk factor for atherosclerotic disease, this study favours the view that after menopause Hcy level increases significantly and a simple non Toxic and relatively inexpensive vitamin (folic acid) intervention might be useful in primary cardiovascular prevention in this high risk group because Hcy is a stronger risk factor for CHD in postmenopausal women than men. Keywords: Menopause, Homocysteine, Folic acid.